Cost based, integrated design optimization using a parametric CAD model. Issue 3 (16th April 2017) - Lin, Than
ABSTRACT: This paper present a novel approach for developing a decision support tool for designers based on manufacturing cost. The approach focuses on exploiting the advantages offered by integrating parametric CAD, manufacturing processing time based cost estimation and optimization technique within an integrated framework. The methodology is then applied in optimizing the geometry for minimum manufacturing cost of rotor blade. GRAPHICAL ABSTRACT: